Hypothermia Protects Mice Against Ischemic Stroke by Modulating Macrophage Polarization Through Upregulation of Interferon Regulatory Factor-4 - Yu X (Dove Medical Press, 2021)
Xinyuan Yu, Yanping Feng, Renzhong Liu, Qianxue Chen Department of Neurosurgery, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People’s Republic of ChinaCorrespondence: Qianxue ChenDepartment of Neurosurgery, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People’s Republic of ChinaTel +86 13607141618Email chen_qx2006@163.comBackground: Therapeutic hypothermia (TH) has been proven to be protective in ischemic stroke (IS) due to its anti-inflammatory capacity. Recently, the interferon regulatory factor 4 (IRF4) has been characterized as a central regulator of neuroinflammation in IS. Here we aim to determine whether IFR4 contributes to the neuroprotective effects of TH in IS.Methods: In the present study, IRF4 knockout (IRF4−/-) and wild-type (IRF4+/+) mice were treated with or without TH after IS. Cerebral IRF4 expression, the production of pro-inflammatory and anti-inflammatory cytokines and macrophage polarization were determined at 8 hours after reperfusion. In addition, cerebral infarct volume and neurological function were evaluated at 7 days after IS.Results: TH attenuates IS together with enhanced IRF4 expression as well as reduced production of pro-inflammatory cytokines. In addition, TH increased M2 macrophage polarization while inhibited M1 macrophage polarization. However, IRF4 knockout worsens neurological outcomes of stoke mice. The expression of pro-inflammatory cytokines were markedly increased in IRF4−/- mice as compared with IRF4+/+ mice at 8 h after stroke. Moreover, IRF4 knockout driven the macrophage polarization toward M1phenotype at 8 h after stroke. Most importantly, IRF4 knockout abolished the neuroprotective and anti-inflammatory effects of TH in IS.Conclusion: Together, we report for the first time that TH attenuates neuroinflammation following IS by modulating M1/M2 macrophage polarization through the upregulation of IRF4 expression.Keywords: therapeutic hypothermia, interferon regulatory factor 4, ischemic stroke, inflammation, macrophage polarization